Efek Kombinasi Aromaterapi Lavender Dan Relaksasi Benson Pada Nyeri Pasien Post Operasi Sectio Caesarea: Studi Kasus - Hanifah, Afi; Risdiana , Nurvita (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
Introduction – Sectio Caesarea (SC) deliveries in Indonesia have increased from 1997 to 2017, from 4.30% to 17%. A common problem that arises as a result of cesarean delivery is post cesarean wound pain. Non-pharmacological management with lavender aromatherapy and Benson relaxation can reduce pain without causing side effects. Objective - To determine the effectiveness of lavender aromatherapy and Benson relaxation on pain levels of postoperative SC patients. Methodology - This study is a case study with descriptive analysis reporting a 25 year old female patient after first day of SC surgery with placental calcification & oligohydramnios. The results of the assessment using the Numeric Rating Scale (NRS) obtained a pain scale of 6 and the patient complained of post-op wound pain. The patient was given nursing care for non-pharmacological therapy with a combination of lavender aromatherapy and Benson relaxation for 1 time in 2 days. Aromatherapy used is lavender essential oil in a humidifier as much as 3 drops, and placed next to the patient with a distance of 60 cm. Then inhale aromatherapy combined with Benson relaxation for 15 minutes. Pain scale was measured before and after non-pharmacological therapy was given. Results – There was a decrease in the pain scale from 6 to 3 after being given non-pharmacological therapy with a combination of lavender aromatherapy and Benson relaxation. Authenticity – This study is an original study on patients with post sectio caesarea (SC)Keywords: pain Post-SC, lavender aromatherapy, Benson relaxation